Vocation and work in the spirit understanding charisms in relation to work and vocation - Puen, Stephanie Ann Y. (2016)
One of the unique aspects of Jesuit Ignatian education is the focus on vocation and discernment. Still, students' misconceptions about vocation are not sufficiently addressed, especially the relation between work and vocation. This paper proposes that Miraslov Volf's pneumatological understanding of work provides insights that can help dispel misconceptions. Understanding one's vocation as a charism can help students make more sense of work in today's context, as well help students understand that work is not simply finding "the right job" that fits their passion and aspiration but also cooperating with and responding to grace in doing the good.
Keywords: Vocation (in religious orders, congregations, etc.); Vocation; Theology